Determinants of social media impact in local government - Mohd Sharif, Mohd Hisham; Troshani, Indrit; Davidson, Robyn (IGI Global, 2016)
Limited attention has been directed towards understanding the impact of social media in the public sector, particularly in local government organisations. Although social media offer substantial benefits and opportunities to local government, research into the impact of social media remains scant. To address this gap, the authors draw on the technology, organisation, and environment (TOE) framework and propose a model of the determinants of social media impact in local government. The model is tested with data collected via a survey with 173 Australian local government organisations using social media. Data were analysed using the partial least squares-structural equation modelling (PLS-SEM) technique. The results indicate that TOE factors including perceived benefits, perceived security risks, compatibility, and degree of formalisation are important predictors of social media impact in local government.